EFFECTS OF INVOLVEMENT IN COMMUNITY EXTENSION PROGRAMS ON STUDENT OUTCOMES - Balila, Jolly S.; Carpizo, Eunice; Rumarate, Maricel; Adanza, Jerome (11th International Scholars Conference, 2016)
Students have been encouraged to become more engaged with the community extension programs and activities. In fact, students’ involvement is one of the accreditation measures. As a result, community engagement activities became a requirement in any academic programs in Higher Education Institution. However, the benefits of student’s involvement should also be assessed. This was conducted to determine the effects of community extension services (CES) involvement on the students’ outcomes. Student outcome was measured in terms of personal (interpersonal skills and intrapersonal skills) and cognitive outcomes in one private Higher Education Institution in the Philippines. A descriptive survey was employed in the study. Data were collected from 270 students who participated in the programs and activities of the CES. The results of the study revealed that the students who were involved in the programs and activities of the CES perceived that their involvement was able to enhance their personal and cognitive outcomes. Some of the benefits of CES involvement were determined. According to the students, CES involvement was perceived to promote their moral development, develops their sense of personal achievement, and improves self and personal identity. Their involvement in CES activities had increased their desire to help others, their understanding of social and cultural differences, and helped improved their better relationship with others. Further results revealed that the effects of the CES involvement were comparable between male and female students. Thus, the community extension programs of the University were effective and therefore may continue in their implementation for the sustainable development of the students and community.